Anatomopathological lesions of infection caused by Platynosomum illiciens (Braun, 1901) in Neotropical primates kept in captivity - Pereira, Washington Luiz Assunção; Conga, David Marcial Fernandez; da Silva, Klena Sarges Marruaz; da Silva, Reinaldo José [UNESP]; Imbeloni, Aline Amaral (Wiley, 2021)
This study described the hepatobiliary anatomopathological lesions associated with trematode Platynosomum illiciens parasitism in Neotropical primates kept in captivity. In the evaluated organs, we observed portal fibrosis, biliary epithelial hyperplasia, and inflammatory reaction with a predominance of lymphocytes and plasmocytes, and in some cases infiltration of eosinophils and neutrophils.
Keywords: hyperplasia; liver fibrosis; Platynosomum; wild primates